2011
DOI: 10.1111/j.1742-4658.2011.08131.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of malic and soluble oxaloacetate decarboxylase enzymes in Enterococcus faecalis

Abstract: Two paralogous genes, maeE and citM, that encode putative malic enzyme family members were identified in the Enterococcus faecalis genome. MaeE (41 kDa) and CitM (42 kDa) share a high degree of homology between them (47% identities and 68% conservative substitutions). However, the genetic context of each gene suggested that maeE is associated with malate utilization whereas citM is linked to the citrate fermentation pathway. In the present work, we focus on the biochemical characterization and physiological co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 44 publications
1
31
0
Order By: Relevance
“…Therefore, we analyzed whether the growth of ABSA and UPSA strains would differ in a synthetic medium that contained a defined amount of malate. For this, we used SHU as defined in previous studies (56)(57)(58) supplemented with 40 mM malic acid, a concentration consistent with prior studies that have used 30 to 50 mM malic acid in vitro (51,(53)(54)(55)(59)(60)(61)(62). We observed that the growth of ABSA 834 and ABSA 729 was significantly higher than the growth of UPSA 058 and UPSA 714 in SHU (Fig.…”
Section: Resultsmentioning
confidence: 54%
See 2 more Smart Citations
“…Therefore, we analyzed whether the growth of ABSA and UPSA strains would differ in a synthetic medium that contained a defined amount of malate. For this, we used SHU as defined in previous studies (56)(57)(58) supplemented with 40 mM malic acid, a concentration consistent with prior studies that have used 30 to 50 mM malic acid in vitro (51,(53)(54)(55)(59)(60)(61)(62). We observed that the growth of ABSA 834 and ABSA 729 was significantly higher than the growth of UPSA 058 and UPSA 714 in SHU (Fig.…”
Section: Resultsmentioning
confidence: 54%
“…Malic acid metabolism is typically associated with an operon comprising genes encoding a malate oxidoreductase enzyme (maeE), a per-mease/transporter (maeP), a transcriptional regulator (maeR), and/or an accessory membrane-anchored sensor kinase (maeK) (53). Bacterial MEs catalyze the oxidative decarboxylation of malate to pyruvate and CO 2 (54), which underpins malolactic fermentation. While there is some evidence that MEs contribute to energy generation and bacterial survival at low pH, a role for MEs in bacterial growth in urine has not previously been investigated.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…London and Meyer (27) reported in their pioneering work on malate metabolism in E. faecalis that the malate transporter and malic enzyme are induced by this substrate and apparently repressed by glucose (25). More recently, we have shown that the E. faecalis mae locus encodes the malate degradative enzymes (5). This locus is composed of two putative divergent operons, maePE and maeKR (Fig.…”
mentioning
confidence: 99%
“…1A). The maeP (EF1207) (35) gene encodes a putative H ϩ /malate symporter, and the maeE (EF1206) (35) gene encodes a malic enzyme that converts malate into pyruvate (5). Pyruvate may be further metabolized via one or a combination of several pathways, depending on the energy needs and redox state of the cell, and is converted to lactate and NAD ϩ (via lactate dehydrogenase), ethanol and NAD ϩ (via alcohol dehydrogenase), or acetate and ATP (via phosphotransacetylase and acetate kinase) (25).…”
mentioning
confidence: 99%